Insights from modern diffuse-flow hydrothermal systems into the origin of post-GOE deep-water Fe-Si precipitates. (15th January 2022) - Dong, Aiguo; Sun, Zhilei; Kendall, Brian; Izon, Gareth; Cao, Hong; Li, Zhihong; Ma, Xiaoming; Yin, Xijie; Qiu, Zhen; Zhu, Xiang-kun; Bekker, Andrey; Poulton, Simon W.
Abstract: Post-GOE deep-water Fe-Si precipitates associated with volcanogenic massive sulfide deposits are an important feature of the Proterozoic rock record. Although it is clear that these enigmatic deposits formed in oxygen-deficient and hydrothermally influenced deep-water settings, the oxidation mechanism(s) resulting in their precipitation remain(s) unclear. Whilst existing genetic models typically couple direct and/or bacterially-mediated iron oxidation with abiotic silica precipitation, low temperature diffuse hydrothermal fluids offer a potential mechanistic alternative to explain the observed layering. Herein, via combination of petrographic observations with elemental and isotopic data (Fe, Si, and O), we explore the genesis of the primary mineral phases present within recent Fe-Si precipitates obtained from the Southwest Indian Ridge. Formation of ferrihydrite and opal-A in these precipitates provides insight into the genesis of widely invoked precursor minerals to post-GOE deep-water Fe-Si precipitates. Specifically, we find that the mineralogical layers that typify these Fe-Si precipitates may have originated via biologically mediated ferrihydrite precipitation and abiotic precipitation of opal-A from oversaturated fluids during diffuse flow. By analogy, we propose that diffuse hydrothermal fluid flow played an important role in the formation of post-GOE deep-water Fe-Si precipitates.